Proceso atención de enfermería en paciente pediátrico con convulsiones. - Salcedo Galarza, Priscila Mercedes (2022)
Seizures or seizures are the most common events in the pediatric population representing a great risk according to the period of time of the same convulsive event the longer the seizures are prolonged, each time it becomes more resistant to the anticonvulsant drug, it also causes an increased risk of morbidity (permanent neurological damage) and mortality. Information of the clinical case developed from the clinical history of a pediatric patient who comes to the hospital of the IESS Babahoyo who comes by emergency area for a seizure evolution of the current disease mother refers clinical picture of pediatric infant for presenting convulsive episodes after suspension of treatment characterized by presenting spasticity and fixed gaze that is subsequently accompanied by fasciculations and movements then is in a state of drowsiness which is decided monitoring in the area of resuscitation, monitor seizures, monitor vital signs every 8 hours and the case is reported to the pediatrics and neurology department for prompt neurological evaluation. Status convulsive a neurological emergency that must be evaluated and treated in an expeditious and adequate way the most frequent causes is poor adherence to treatment for epilepsy the definitive diagnosis is with an electroencephalogram.